ANALISIS PEMANFAATAN MEDIA FLASHCARD BERBASIS AUGMENTED REALITY DALAM PEMBELAJARAN SEKOLAH DASAR - Kornia Sari, Desi; Fajriah, Febi; Efendi Hutagalung, Erwin; Muhammadin Al Fath, Ayatullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational media are tools that can help students understand various subjects. The purpose of this study is to analyze the use of Augmented Reality-based flashcards in elementary school education. Thus, the researcher can draw upon various references from previous research and the insights of earlier researchers to present relevant information to readers. The background of this study is based on the need for innovation in educational media to enhance students’ interest, motivation, and understanding through the use of digital technology. This is a qualitative study employing a systematic literature review method, specifically by examining 20 articles as a sample sourced from Google Scholar, covering the past five years of publication. Based on the results of the systematic literature review, it was found that the use of Augmented Reality-based flashcard media has the potential to create more engaging, interactive, and contextual learning experiences. This learning medium leverages technology to provide educators with opportunities to innovate in its application. The conclusion that can be drawn from this study is that the use of Augmented Reality-based flashcard media in elementary schools can be an innovative alternative, provided that there is support for facilities and improvements in teacher competencies so that its implementation can be effective.